The neuroinvasiveness, neurotropism, and neurovirulence of SARS-CoV-2. Issue 5 (May 2022) - Bauer, Lisa; Laksono, Brigitta M.; de Vrij, Femke M.S.; Kushner, Steven A.; Harschnitz, Oliver; van Riel, Debby
Abstract : Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection is associated with a diverse spectrum of neurological complications during the acute and postacute stages. The pathogenesis of these complications is complex and dependent on many factors. For accurate and consistent interpretation of experimental data in this fast-growing field of research, it is essential to use terminology consistently. In this article, we outline the distinctions between neuroinvasiveness, neurotropism, and neurovirulence. Additionally, we discuss current knowledge of these distinct features underlying the pathogenesis of SARS-CoV-2-associated neurological complications. Lastly, we briefly discuss the advantages and limitations of different experimental models, and how these approaches can further be leveraged to advance the field. Highlights: Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection has been shown to be associated with a range of neurological complications during the acute and postacute phases. The pathogenesis of SARS-CoV-2-associated CNS disease is complex and diverse, and cannot be explained by one sole mechanism. To understand the pathogenesis of SARS-CoV-2-associated CNS disease, it is important to gain deeper insights into the neuroinvasiveness, neurotropism, and neurovirulence of SARS-CoV-2. It is also imperative to consider the kinetics, since a viral infection is not a static event. Relevant in vivo models can be used to study the neuroinvasiveness, neurotropism, and neurovirulence of SARS-CoV-2, and in vitro human pluripotent stem cell (hPSC) models can be used to study the neurotropism of the virus and the associated cellular responses. These models may be further leveraged to study differences among SARS-CoV-2 variants and for the design of therapeutic approaches.